Cost‐effectiveness analysis of two attachment systems for mandibular overdenture. Issue 7 (21st April 2020) - Matthys, Carine; De Vijlder, William; Besseler, Jos; Glibert, Maarten; De Bruyn, Hugo
Abstract: Objectives: This study analysed the cost‐effectiveness of two different attachments for the 2‐implant overdenture (2IOD) in edentulous mandibles. Materials and methods: When considering alternative treatments, cost‐effectiveness analysis is an important factor for stakeholders (patient, clinician, social security, insurance company, etc.). A general practice population ( n = 116) was treated between 2003 and 2013 with a mandibular 2IOD with 2 different ball/stud attachment systems, one spherical (Group D) and one cylindrical (Group L). Patient well‐being was assessed with OHIP‐14‐Total (OHIP‐14‐T), at intake and annually up to 5 years, to calculate the health effect. Initial and maintenance costs of both treatments were inventoried. The cost‐effectiveness was compared. Annual discount rates of 4% and 1.5% were applied to future costs and health outcomes, following Dutch guidelines. Prices were adjusted to the year 2003. To offset the uncertainty in relevant input parameters, a sensitivity analysis was performed using bootstrap analysis. Significance was set at p < .05. Results: The health effect was 6.36 ( SD 5.32) for Group D and 8.54 ( SD 5.63) for Group L. The sum of the discounted costs up to 5 years was EUR 4, 210.98 ( SD 634.75) for the D and EUR 3, 840.62 ( SD 302.63) for the Group L ( p = .005). The bootstrapping reports that L abutment clearly dominates the D abutment in terms of cost‐effectiveness. Conclusions: The 2IOD on the L abutment is dominant compared to the 2IOD on D abutment, in a 5‐year perspective.